The Cambridge Bible commentary : the books of Amos, Hosea and Micah - McKeating, Henry; McKeating, Henry (Cambridge, Cambridge University Press, 1971)
The plan of this volume of commentary on the New English Bible text of three Old Testament books follows the pattern established by the New Testament series of Cambridge Bible Commentaries on the New English Bible. The main divisions of the text are those provided by the New English Bible itself. The text is further subdivided for the purposes of the commentary, which is printed in short sections following the relevant portion of text. In his introduction Dr McKeating discusses the chronology of the books in this volume, indicating briefly the historical events of the period. He examines the structure and content of these books and shows how these three men, alike in their intensity but utterly different in background and in temperament, reflect three different attitudes to a corrupt society.
Israel and Judah in the eighth century -- When did Amos prophesy? -- When did Hosea prophesy? -- When did Micah prophesy? -- What is a prophet? -- What is different about the eighth-century prophets? -- The materials of the prophetic books -- The structure of the prophetic books -- The Book of Amos -- The Book of Hosea -- The Book of Micah.
Cover title: Amos, Hosea, Micah.
Includes bibliographical references (page 194) and index.
Keywords: Bible -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries